Information Poverty: Kemiskinan Informasi dan Peranan Perpustakaan dalam Pengentasannya - Himayah, Himayah (Jurnal Ilmu Perpustakaan & Informasi KHIZANAH AL-HIKMAH, 2013)
Information and communication technology (ICT) plays an important role in classifying the world in information richand information poor. Poverty is not only limited information by "people who mastered the technology" and "people who do not master the technology". More complex phenomenon, including language and cultural diversity issues, level of education and the ability to access information and take advantage of that information. There are several factors that cause information poverty. Among othersare access to information , socio-economic factors and the factor of information infrastructure and information context of each individua . To overcome the problem, the solutionsare the presence of informationequality, and information literacy skills. Information literacy is a set of skills to know when an information is needed, and where the information located, evaluation and the use of the information effectively. Good library can play its role in nformation equality and sharing, by providing various forms of means of information and all of them can be freely and widely used by those who need it.